Let and β are the roots of the given eqn
Sum of the roots = = =
Product of the roots = = = =
= = Using (a + b)2 = a2 + b2 + 2ab
On substituting values from above, we get
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation